O ensino de isomeria óptica por meio de atividades experimentais - Sulzbach, Ana Cristina (2017)
In order to contribute to the teaching and learning of chemistry, this research is presented and it proposes an alternative methodology to the study of scientific concepts in optical isomerism. The choice of this subject is due to its great importance in pharmacology due to the fact that many prescribed drugs employ enantiomers of active compounds, bearing in mind the tragedy due to talidomida around the sixties, hence we judge the learning of this concepts, a matter of prime importance for the chemistry student. By knowing that the contentes is considered too abstract and theoretical, the main difficulties presented in the teaching and learning of optical isomerisms are identified in order to propose a study of the following concepts: light, dichroism, polarizers, birrefringence, light polarization from physics and the insertion of these concepts to derive relevant chemical concepts like optical activity, quirality, molecular asymmetry. These issues were worked on by students through experimental activities under a constructivist learning environment in which students acquired their own knowledge through interaction with lab instruments and group discussion. The didactic materials used in this work were all constructed by the author. The series of activities were done in a classroom of first year pharmacy students and they were made towards the application of concepts of isomery to selected issues on modern pharmacological research, expecting to motivate the students for their professional formation. The activities were evaluated through textual discusive analysis. The results allowed us to conclude that the activities involved as well as the didactic materials were suitable in satisfying the expected aims of this research and, therefore, we concluded that this proposal allowed a better teaching and learning of concepts of optical isomerism for introductory university general chemistry courses.